Automatic Lecture Recording and Broadcasting (International Journal of Engineering and Computer Science, 2014)
Lecture recording has a significant role in online learning and distance education. Usually lectures are recorded by a cameraman or a stationary camera. The recorded video consists of the complete training room including trainer, students and the projector screen. In regular lectures, presenter will speak more than changing presentation slides; hence more time will be spent in explaining the slide. Video recording of such lectures will not have changes in consequent frames. In this project, we propose an intelligent lecture recording & broadcasting system that will automatically filter out the projector screen and the presenter face if it appears in front of the screen. Optimal video with changed images will be distributed to all the students through online streaming.